Royal life in Mānasôllāsa - Arundhati, P. (Sundeep Prakashan, 1994)
Study of Mānasôllāsa, also known as Abhilāṣitārthacintāmaṇi, of Someśvara III, Chalukya Emperor, 12th cent., an encyclopaedic work on topics connected with a royal house-hold and royal court.
Includes bibliographical references (p. 183) and index.
Study of Mānasôllāsa, also known as Abhilāṣitārthacintāmaṇi, of Someśvara III, Chalukya Emperor, 12th cent., an encyclopaedic work on topics connected with a royal house-hold and royal court.
Keywords: Learning and scholarship / India.